(untitled) (Journal of actual problems of jurisprudence, 2019)
When studying the problems of conflict and social deviations in the behavior of minors, it is necessary to proceed from the general thesis that the epistemological roots of the study of conflict problems are interdisciplinary, suggesting an integrated approach to solve them using many scientific sciences: philosophy, logics, sociology, law, pedagogy, psychology, psychiatry, etc. Among the various areas of legal sociology, legal (conflict) conflictology is becoming increasingly important, which studies legal relations, norms and institutions from the point of using them to prevent and resolve conflicts. This problem in legal science is new for two reasons: firstly, due to the insufficiency of the development of general conflictology as an independent integrated socio-psychological discipline; secondly, the dogmatic study of law without studying the nature of conflict and social deviations in the behavior of minors does not contribute to its broader understanding, including as an instrument for dealing with social and psychological conflicts. Key words: conflict, conflictology, social deviations, deviant behavior, minor, socialization, social contradictions, offenses, social control, control measures, punishment.